rTiWIM: uma ferramenta para elicitação e validação de requisitos de software utilizando linguagem de interface - Araújo, João Victor Rocha (2024)
The process of requirements gathering is one of the fundamental stages in the software product lifecycle. In the context of software development, there is an increasing need for tools that support stakeholders in the process of eliciting and validating system requirements. The involvement of the end-user in this process strengthens the communication between interested parties, leading to new discoveries and potential issues the system might present. Thus, this dissertation proposes a support tool for system stakeholders, named rTiWIM, which will utilize the TiWIM communication model to elicit and validate software requirements in web systems through interface language. The tool will provide the following functionalities: (i) user registration, (ii) page validation, (iii) registration of pages for validation, (iv) online chat, and (v) evaluations carried out by end-users, as well as a collaborative environment to facilitate communication among stakeholders. To evaluate the tool, a focus group was conducted with developers and professionals in the field to assess the relevance of the tool and test its functionalities in practice, along with an empirical evaluation using a real system under development. Based on the arguments from the groups and feedback received during the empirical test, it was possible to identify improvements in the application as well as the benefits generated in the communication among stakeholders involved in system development.